Slovenia and Austria at the crossroads of mutual relations. Slovene-Austrian relations as hostage of the troubled legacy of the 19th and 20th centuries - Grafenauer, Danijel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
Austria and Slovenia are neighbours and friends, closely linked both geographically and historically. Over time, their peoples have developed various perceptions, stereotypes, and prejudices about each other. The rise of national movements and modern states has significantly shaped national historiographies, which have often drawn on past events in search of foundational ideas for the formation of their respective nationstates. This paper explores how this complex and sometimes troubled legacy has influenced cross-border relations.
Keywords: Austria; Avstrija; cross-border relations; čezmejni odnosi; history; Slovenia; Slovenija; stereotipi; stereotypes; zgodovina